1995
DOI: 10.1007/bf01837402
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Na+ and Mg2+ ions in acetylcholine receptor channels of frog skeletal muscle changes in character with an increase in agonist concentration

Abstract: Measurements of agonist-induced single-channel currents of nicotinic acetylcholine receptor channels (nAChR) have shown that addition of divalent metal cations (Ca2+, Mg2+, Ba2+) in millimolar amounts causes a decrease of 40% or more in currents carried by monovalent cations (Na+, Cs+). Conventional voltage-clamp measurements were made at frog (Rana pipiens) sartorius endplates to determine if this occlusive interaction between mono- and divalent cations is preserved in macroscopic currents produced by higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 20 publications
(33 reference statements)
4
10
1
Order By: Relevance
“…Conversely, channel activation was lengthened with 0.1 µM ACh, but not with 100 µM. Thus we found no single-channel correlate of the reported conversion of Mg 2+ action from inhibition to facilitation with increasing agonist concentration [19]. This discrepancy might be due to the different experimental preparations used (developing mouse or adult frog), or to the facilitation being specific for the conditions (high [Mg 2+ ] e and carbamylcholine as an agonist used in [19]).…”
Section: Effects Of Cacontrasting
confidence: 70%
See 1 more Smart Citation
“…Conversely, channel activation was lengthened with 0.1 µM ACh, but not with 100 µM. Thus we found no single-channel correlate of the reported conversion of Mg 2+ action from inhibition to facilitation with increasing agonist concentration [19]. This discrepancy might be due to the different experimental preparations used (developing mouse or adult frog), or to the facilitation being specific for the conditions (high [Mg 2+ ] e and carbamylcholine as an agonist used in [19]).…”
Section: Effects Of Cacontrasting
confidence: 70%
“…It is also unclear whether the single-channel properties of AChR channels are differently affected by Mg 2+ at various [ACh]. In fact, at variance with "classical" studies, a conversion of Mg 2+ action from block to facilitation of carbamylcholine-evoked responses is observed at the frog neuromuscular junction with high agonist concentrations [19]. Furthermore, there is no general consensus on the effects of divalent cations on the kinetics of AChR channels.…”
Section: Introductionmentioning
confidence: 99%
“…Means of 45 digitized samples of both clamping current and voltage (sampling rate = 100 Hz) were computed at consecutive 0.5-s intervals throughout each experimental trial and stored (64 K Apple II series desktop computer) for later analysis using specialized programs. Previous publications [39,40] should be consulted for further details about the methods used in voltage clamping and agonist superfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Since the open-state configuration of channel proteins, particularly in the narrow pore region of nAChR, shapes and limits ion traffic through the channel [11,14,28,32,57,60], a possible approach to the question of agonist-dependent secondary open states might be to examine the "mix" of ion species making up nAChR currents at various increasing concentrations of agonists and to see if there is any shift in the preference or interaction among permeating cations. In a preliminary study, in which something of this kind was tried using Na + and Mg 2+ as convenient current carriers with readily distinguishable characteristics [40], it was found that above a certain submaximal "transition" level of agonist (lying between 50 and 100 µM carbamylcholine) the peak Mg 2+ current began to increase disproportionately to the rise of Na + currents and with changes in the composite bi-ionic currents that were most easily explained in terms of altered open states characterized by decreased ion-channel interactions in the pore region and greater independence of the Na + and Mg 2+ fluxes. This proposal is complicated, however, by some other possible actions involving Mg 2+ outside the pore region, including displacement of agonist molecules from outer receptor sites [53,56], and Mg 2+ -specific effects on intracellular phosphorylation pathways [2] which could lead to the opening of other ion channels such as L-type Ca 2+ channels [21,50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation